Synthesis, polymerization ability, nonlinear optical properties of methacrylic monomers and polymers with benzylidene moiety - Smokal, Vitaliy; Krupka, Oksana; Kolendo, Aleksey; Derkowska, Beata; Czaplicki, Robert; Sahraoui, Bouchta (Publishing House of Lviv Polytechnic National University, 2007)
Синтезованo нові метакрилові мономери та полімери з бензиліденовим фрагментом. Структура всіх сполук доведена методами ПМР та УФ- спектроскопією. Нелінійно-оптичні властивості третього порядку оксазолон, -тіозолідінон- та тіогідантоїн- вмісних похідних досліджені в розчині методом змішування чотирьох хвиль (DFWM) з довжиноюхв илі532 нм. Одержана залежність для ацетильних похідних оксазолонів, тіозолідінонів, тіогідантоїнів: p-1b> p-3b >p-2b. Показано, що значення нелінійно-оптичної чутливості третього порядку ( χ <3> ) кополімеру вищі порівняно з відповідним гомополімером, а длямодельних сполук метакрилових мономерів вищі, ніж для полімерів завдяки стеричним ефектам. New methacrylic monomers and polymers with benzylidene fragment have been synthesized. Structures of all compounds have been determined by 1H NMR and UV spectroscopy. The third order nonlinear optical properties of oxazolone, thiazolidinone and thiohydantoin containing derivatives have been investigated in solutions using degenerate four wave mixing method (DFWM) at 532 nm wavelength region. The dependence p-1b> p-3b> >p-2b for acetyl derіvatives of oxazolone, thiohydantoin and thiazolidinone has been found. It has been shown that the third order nonlinear optical susceptibility (χ <3> ) of copolymer is higher than that of the corresponding homopolymer, and for the modeling compounds of methacrylic monomers it is higher than for polymers due to the steric factor.
Синтез, полімеризаційна здатність, нелінійно-оптичні властивості метакрилових мономерів та полімерів з бензиліденовим фрагментом
Keywords: оксазолон; тіогідантоїн; арил(мет)акрилати; радикальна полімеризація; нелінійно-оптичні властивості; oxazolone; thiazolidinone; thiohydantoin; aryl(meth)acrylates; radical polymerization; nonlinear optical properties